Thermal management device with boiling-driven heat spreader - Lim, Hyunmuk; Shin, Dong Hwan; Rhee, Gwang Hoon; You, Seung M.; Lee, Jungho (38th Annual Semiconductor Thermal Measurement, Modeling and Management Symposium, SEMI-THERM 2022 - Proceedings, 2022)
High-powered electronics are limited by thermal management issues of the heat losses and might be led to failure. The increasing heat load requires higher thermal management measures, and one of them is a heat spreader using phase change heat transfer. In particular, a boiling-driven heat spreader can be used even at high heat flux. In this study, thermal management of a local heat source generating a heat flux of up to 100 W/cm2 was performed through air cooling in an environmental chamber at 45°C. As a result, it was possible to cool the junction temperature to within 100°C through an air-cooling heat sink integrated with a boiling -driven heat spreader.
Keywords: Air cooling; Heat spreaders; High heat flux; High thermal; Local heat source; Management issues; Management measures; Phase change heat transfer; Thermal; Thermal management devices